2003
DOI: 10.1097/00005537-200312000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Collagen in the Lamina Propria of the Human Vocal Fold

Abstract: This basket-like configuration better explains how the vocal fold is able to stretch even though it contains nonstretchable fibers and to modulate the frequency of the voice under the action of the intrinsic musculature of the larynx. Segmental areas of disarray of the basket-like structure of the collagen layers were systematically observed in older patients. Thus, it is possible that vocal alterations occurring in the elderly might be the result of a loss of histoarchitectural arrangement of the collagen sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 13 publications
4
67
0
4
Order By: Relevance
“…The picrosirius stain showed abundant type I collagen but little in the way of Type III collagen within the elderly LP. This finding is supported by Melo et al (2003) who reported that in older vocal folds the proportion of Type I collagen is increased compared with Type III. Wang et al (2008) notes that Type III collagen becomes abundant compared with Type I collagen during tissue repair and proliferation, perhaps suggesting that the regenerative capacity of the fibroblasts within the VF LP is somewhat constrained in the elderly.…”
Section: Discussionsupporting
confidence: 68%
“…The picrosirius stain showed abundant type I collagen but little in the way of Type III collagen within the elderly LP. This finding is supported by Melo et al (2003) who reported that in older vocal folds the proportion of Type I collagen is increased compared with Type III. Wang et al (2008) notes that Type III collagen becomes abundant compared with Type I collagen during tissue repair and proliferation, perhaps suggesting that the regenerative capacity of the fibroblasts within the VF LP is somewhat constrained in the elderly.…”
Section: Discussionsupporting
confidence: 68%
“…The accumulation of these proteins is of particular interest because they comprise the principle fibrous and interstitial proteins present within the human vocal fold [21][22][23]. The identification of strategies that accelerate the synthesis, accumulation and harvesting of these biomaterials may lead to the Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the papers on the larynx have studied the mucosal layer that lines the vocal folds; various modifications have been described, such as: the reduced number of elastic fibers in the middle layer of the lamina propria; 1 the reduced density of epithelial cells and the thickness of the lamina propria; 2,3 the increased quantity of collagen in the lamina propria; 4 morphological changes in elastic fibers located in the superficial layer of the lamina propria; 5 and collagen fiber architectural derangement in the lamina propria. 6 Studies on the laryngeal muscle system have revealed results that suggest the following: a reduced number of muscle fibers in the thyroarytenoid muscle, particularly slow contraction muscle fibers, 7 and a reduced amount of those proteins that are responsible for muscle contraction. 8 Based on electromyography studies, other authors have presented results that suggest denervation or axonal injury involving laryngeal motor control in the elderly, leading to altered contraction of laryngeal muscles.…”
Section: Introductionmentioning
confidence: 99%